Social Participation of Frail Older People with Functional Limitations Ageing Alone in Place in Italy, and Its Impact on Loneliness: An Urban–Rural Comparison - Maria Gabriella Melchiorre; Marco Socci; Giovanni Lamura; Sabrina Quattrini (Urban Science, 2025)
(1) Background: Older people ageing in place alone with functional limitations experience several difficulties in daily life, potentially hampering their social participation. This in turn could impact their perceived loneliness. This paper aims to investigate these issues based on findings from the IN-AGE (“Inclusive ageing in place”) study carried out in 2019 in Italy. (2) Methods: The focus of this paper is on the Marche region (Central Italy), where 40 qualitative/semi-structured interviews with seniors were administered in both urban and rural sites. A content analysis was carried out, in addition to some quantification of statements. (3) Results: Older people are mainly involved in receiving/making visits, lunches/dinners with family members and friends, religious functions, walking, and watching television (TV). Overall, the more active seniors are those living in rural sites, with lower physical impairments, and with lower perceived loneliness, even though in some cases, a reverse pattern emerged. The results also indicate some different nuances regarding urban and rural sites. (4) Conclusions: Despite the fact that this exploratory study did not have a representative sample of the target population, and that only general considerations can be drawn from results, these findings can offer some insights to policymakers who aim to develop adequate interventions supporting the social participation of older people with functional limitations ageing in place alone. This can also potentially reduce the perceived loneliness, while taking into consideration the urban–rural context.